The health and welfare effects of environmental governance: Evidence from China - Chan Wang; Lianggui Liao; Xue-mei Zhang; Lu-tong Lin; Bin Chen (Environment International, 2024)
Environmental regulations aim to reduce pollution and improve air quality and the health of residents. However, there is a lack of research focusing on the health and welfare effects of low-carbon city pilot policies. In this context, this study takes China’s low-carbon city pilot policy as an entry point, focuses on the health effects of public environmental governance, and systematically investigates the effects and mechanisms of low-carbon city development on the health of middle-aged and elderly people by applying the difference-in-differences method. The study finds that low-carbon city (LCC) policy significantly improves the physical and mental health of middle-aged and elderly people, and the main transmission mechanism is the reduction in air pollution and improvement in social capital. These results hold following a series of robustness tests. Furthermore, low-carbon city construction can reduce hospitalization and outpatient costs for people over 45 years old by up to 3 % and 15.5 %, respectively. The findings of this study provide useful policy insights for ensuring sustainable improvement in environmental quality and public health.